Anna Hazare: A Corruption Crusader and His Grassroots Wisdom. (October 2017) - Chowdhury, Rashedur; Banerjee, Sourindra; Nagarkoti, Deepak Singh
This article explores the fight against corruption through the eyes of Anna Hazare, a renowned social activist from India, who spent more than 35 years of his life fighting corruption. Anna Hazare provides a detailed description of the anti-corruption movement he has led, provides his views on the World Bank guidelines to lower corruption, and highlights the need for sacrifice and righteousness on the part of leaders who fight corruption. The article presents insights into these concepts, which deserve greater attention from organization scholars and must be researched further if the literature on corruption is to be enriched.